Оптимальний метод ендоскопічної адреналектомії за пухлин правої та лівої надниркових залоз - Грубнік, В. В.; Бурлак, О. С.; Ільяшенко, В. В. (Clinical Endocrinology and Endocrine Surgery, 2009)
From 1995 we have executed 79 endoscopic adrenalectomies, 33 — right-side, 46 — left-side (20 — transperitoneal, 26 — were executed by retroperitoneal access). The group of comparison was made of 37 patients operated by laparotomic and lumbotomic method. Among indications to the operation for 33 patients (41,7%) was the Conn syndrome, Cushing syndrome — 15 (19%), cortizolprodoucing carcinoma — 1 (1,27%), hormonal non-active adenomas — 28 (35,44%), hormonal non-active carcinoma of the adrenal — 1 case (1,27%). Right-side laparoscopic adrenalectomy was executed by transperitoneal access in position of patient on the back. At the beginning of left-side adrenalectomy we executed by the transperitoneal access. Afterwards during the left-side adrenalectomy we refused from transperitoneal access because of large technical difficulties and possible injuries, closeness of large main vessels, spleen, pancreas and more great risk of complications. Nowadays the interventions at the left adrenals are executed by retroperitoneal access.